Influence of fused deposition modelling printing parameters on tablet disintegration times: a design of experiments study - Kreft Klemen; Stanić Tijana; Perhavec Petra; Dreu Rok; Lavrič Zoran (Acta Pharmaceutica)
Despite the importance of process parameters in the printing of solid dosage forms using fused deposition modelling (FDM) technology, the field is still poorly explored. A design of experiment study was conducted to understand the complete set of process parameters of a custom developed FDM 3D printer and their influence on tablet disintegration time. Nine settings in the Simplify 3D printing process design software were evaluated with further experimental investigation conducted on the influence of infill percentage, infill pattern, nozzle diameter, and layer height. The percentage of infill was identified as the most impactful parameter, as increasing it parabolically affected the increase of disintegration time. Furthermore, a larger nozzle diameter prolonged tablet disintegration, since thicker extruded strands are generated through wider nozzles during the printing process. Three infill patterns were selected for in-depth analysis, demonstrating the clear importance of the geometry of the internal structure to resist mechanical stress during the disintegration test. Lastly, layer height did not influence the disintegration time. A statistical model with accurate fit (R2 = 0.928) and predictability (Q2 = 0.847) was created. In addition, only the infill pattern and layer height influenced both the uniformity of mass and uniformity of the disintegration time, which demonstrates the robustness of the printing process.